Photoinduced Reduction of PtIV within an Anti‐Proliferative PtIV–Texaphyrin Conjugate. Issue 29 (26th June 2014) - Thiabaud, Grégory; Arambula, Jonathan F.; Siddik, Zahid H.; Sessler, Jonathan L.
Abstract Invited for the cover of this issue are the groups of Jonathan Sessler at The University of Texas at Austin and Zahid Siddik at The University of Texas M.D. Anderson Cancer Center in Houston, Texas. The cover picture depicts a tumor‐targeting texaphyrin platinum(IV) conjugate that undergoes controlled reduction and subsequent release of the platinum moiety that can then bind DNA. This conjugate is found to inhibit cell proliferation in ovarian cancer cell lines. Read the full text of the article at 10.1002/chem.201403094.